Cellulose Fiber-Reinforced PLA versus PP. (4th July 2017) - Graupner, Nina; Müssig, Jörg
Abstract : The present study focuses on a comparison between different cellulose fiber-reinforced thermoplastics. Composites were produced with 30 mass-% lyocell fibers and a PLA or PP matrix with either an injection (IM) or compression molding (CM) process. Significant reinforcement effects were achieved for tensile strength, Young's modulus, and Shore D hardness by using lyocell as reinforcing fiber. These values are significantly higher for PLA and its composites compared to PP and PP-based composites. Investigations of the fiber/matrix adhesion show a better bonding for lyocell in PLA compared to PP, resulting in a more effective load transfer from the matrix to the fiber. However, PLA is brittle while PP shows a ductile stress-strain behavior. The impact strength of PLA was drastically improved by adding lyocell while the impact strength of PP decreased. CM and IM composites do not show significant differences in fiber orientation. Despite a better compaction of IM composites, higher tensile strength values were achieved for CM samples due to a higher fiber length.